(untitled) (Biological Sciences - PJSIR, 2003)
The effluents (distillate) obtained during air blowing of asphalt in presence of metallic salts, were evaluated for their amount, gravity and acidic content. The acidic gases decrease the life of the plant and cause environmental problems. During a 15 h air oxidation (blowing) period, it was observed that for feed-I, amount and acidity were effected by the catalysts. Variation in the amount and gravity of effluents during feed II and III air blowing was not so distinct as with feed I. This indicates that the extent of amount and acidic content of the effluents also depend on the composition of feed.